“Graffiti, black and lesbian writers”: the writing of feminist graffiti in the city of Salta, Argentina (2020)
The article shows part of the transformations that feminist graffiti writing introduces in the city of Salta-Argentina, and how these make up a new and alternative visual repertoire in the urban landscape. Feminist and transfeminist graffiti refer to that anonymous writing on walls and streets of urban space, whose emergency context refers to the mobilizations organized by feminist groups. It analyzes from an intersectional approach and a gender perspective, those social processes of construction and spatial differentiation in the city, and the power relations that cross them. It seeks to contribute, in constant dialogue with the communicational studies of the city and graffiti, to the understanding of the differentiated uses that women, lesbians, and trans identities make of space.